Binary classification SVM-based algorithms with interval-valued training data using triangular and Epanechnikov kernels - Utkin, Lev V.; Chekh, Anatoly I.; Zhuk, Yulia A. (Neural networks, 2016)
Classification algorithms based on different forms of support vector machines (SVMs) for dealing with interval-valued training data are proposed in the paper. L2-norm and L∞-norm SVMs are used for constructing the algorithms. The main idea allowing us to represent the complex optimization problems as a set of simple linear or quadratic programming problems is to approximate the Gaussian kernel by the well-known triangular and Epanechnikov kernels. The minimax strategy is used to choose an optimal probability distribution from the set and to construct optimal separating functions. Numerical experiments illustrate the algorithms.